2021
DOI: 10.3390/ani11072141
|View full text |Cite
|
Sign up to set email alerts
|

Do You Think I Am Living Well? A Four-Season Hair Cortisol Analysis on Leisure Horses in Different Housing and Management Conditions

Abstract: The satisfaction of leisure horses’ behavioral needs has begun to be considered a priority, linked to the awareness that horses kept in single boxes may be deprived of social contact and the possibility to perform natural behaviors. Several factors may influence horses’ quality of life also in the paddock, and there are very few data on the effects of those variables on leisure horses’ chronic stress, measurable in terms of activation of the hypothalamic–pituitary–adrenocortical axis. Therefore, managerial cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 40 publications
1
22
1
Order By: Relevance
“…Being housed individually within boxes could also induce aggressiveness toward humans [ 26 ]. Mazzolaet al [ 13 ] has recently reported that hair cortisol concentration was significantly lower in horses that spent the night indoors, suggesting the best homeostasis for these subjects. This is in agreement with the results of this study where the hair cortisol levels in free-ranging horses were significantly higher compared to those found in police horses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Being housed individually within boxes could also induce aggressiveness toward humans [ 26 ]. Mazzolaet al [ 13 ] has recently reported that hair cortisol concentration was significantly lower in horses that spent the night indoors, suggesting the best homeostasis for these subjects. This is in agreement with the results of this study where the hair cortisol levels in free-ranging horses were significantly higher compared to those found in police horses.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study that has used the LC-MS/MS technique for detecting cortisol from horsehair. All the previous studies used immunoassays or ELISA for hair cortisol measurements on horsehair [ 11 , 13 , 21 , 29 , 30 ]. These assays are based on interactions between antigens and antibodies, and are therefore prone to biases due to “similar” molecules, such as other steroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, an illness condition such as the equine squamous gastric disease (ESGD) was evaluated in terms of stress by Prinsloo and coworkers [12] using an ELISA method. To the best of our knowledge, in the following years, only other seven manuscripts have been published [1,[13][14][15][16][17][18]. With regard to sampling body region, mane and withers have been chosen more often [10,12,15,19].…”
Section: Overview Of the Methods For Hcc Determinationmentioning
confidence: 99%
“…The limits of detection (LOD) of the published methods were at ppb or sub-ppb levels, but often they were not provided. Particularly, only six papers provided the LODs referred to the sample [9,11,14,16,17]. The detected HCC levels were generally very different, probably also because of the known limitations of immunoassays, considering no study analyzed PBs to evaluate the interferences.…”
Section: Overview Of the Methods For Hcc Determinationmentioning
confidence: 99%